Myomedin replicas of gp120 V3 loop glycan epitopes recognized by PGT121 and PGT126 antibodies as non-cognate antigens for stimulation of HIV-1 broadly neutralizing antibodies - Daniel Lišková, Veronika; Kosztyu, Petr; Kuchař, Milan; Černý, Jiří; Bharadwaj, Shiv; Petroková, Hana; Vroblová, Eliška; Křupka, Michal; Malý, Michal; Zosinčuková, Tereza; Šulc, Josef; Rašková Kafková, Leona; et al. (Frontiers in Immunology, 2022)
Imprinting broadly neutralizing antibody (bNAb) paratopes by shape complementary protein mimotopes represents a potential alternative for developing vaccine immunogens. This approach, designated as a Non-Cognate Ligand Strategy (NCLS), has recently been used for the identification of protein variants mimicking CD4 binding region epitope or membrane proximal external region (MPER) epitope of HIV-1 envelope (Env) glycoprotein. However, the potential of small binding proteins to mimic viral glycan-containing epitopes has not yet been verified. In this work, we employed a highly complex combinatorial Myomedin scaffold library to identify variants recognizing paratopes of super candidate bNAbs, PGT121 and PGT126, specific for HIV-1 V3 loop epitopes. In the collection of Myomedins called MLD variants targeted to PGT121, three candidates competed with gp120 for binding to this bNAb in ELISA, thus suggesting an overlapping binding site and epitope-mimicking potential. Myomedins targeted to PGT126 designated MLB also provided variants that competed with gp120. Immunization of mice with MLB or MLD binders resulted in the production of anti-gp120 and Env serum antibodies. Mouse hyper-immune sera elicited with MLB036, MLB041, MLB049, and MLD108 moderately neutralized 8-to-10 of 22 tested HIV-1-pseudotyped viruses of A, B, and C clades in vitro. Our data demonstrate that Myomedin-derived variants can mimic particular V3 glycan epitopes of prominent anti-HIV-1 bNAbs, ascertain the potential of particular glycans controlling neutralizing sensitivity of individual HIV-1 pseudoviruses, and represent promising prophylactic candidates for HIV-1 vaccine development.